Respuesta :

Step-by-step explanation:

A....

Solution ,

[tex] = \frac{h - 3}{3} = 3h \\ [/tex]

[tex] = h - 3 = 9h[/tex]

[tex] = h - 3 - 9h = 0[/tex]

[tex] = h - 9h = 3[/tex]

[tex] = - 8h = 3[/tex]

Change the sign of both side

[tex] = 8h = - 3[/tex]

[tex] = h = - \frac{3}{8 } \\ [/tex]

B....

Solution,

[tex] = \frac{t}{2} = \frac{t + 1}{5} \\ [/tex]

Multiply the both side by the least common multiple to eliminate the fraction...

[tex] = 5t = 2t + 2[/tex]

[tex] = 5t - 2t = 2[/tex]

[tex] = 3t = 2[/tex]

[tex] = t = \frac{2}{3} \\ [/tex]